JURIDICAL ASPECTS OF UNDERAGE MARRIAGE AND CUSTOMARY LAW - Royani, Esti; Nurtjahjo, Arief; Bilung, Norti; Sajid Ali (Awang Long Law Review, 2023)
In Mahakam Ulu Regency, underage marriages occur, where men are only 16 years old and women are 14 years old. From a positive legal perspective, underage marriage is very unusual for those who marry at a very young age, from a legal perspective it can violate Law Number 35 of 2014 the role of parents to prevent underage marriages in this case is contrary to the Act. Child Protection Act. Throughout 2019, in Mahakam Ulu Regency in the past year, according to research recorded at the Population and Civil Registration Office in Mahakam Ulu Regency, 20 underage couples got married. The majority of couples who marry underage are pregnant out of wedlock due to promiscuity. Of the twenty couples, the village with the highest number of child marriages compared to other villages, namely six couples, occurred in Mahakam Ulu Regency. empirical juridical research, research using field data. The results showed that the Juridical Aspects of Underage Marriage according to Indonesian Positive Law can be seen in the provisions of Law Number 16 of 2019 concerning Marriage Article 7 paragraph (1) Marriage is only permitted if the man has reached the age of 19 years and the woman has reached the age of 19 years. Article 6 paragraph (2) To carry out a marriage, a person who has not reached the age of 21 years must obtain permission from both parents and Law Number 23 of 2002 concerning Child Protection Article 26 (1) Parents are obliged and responsible for: caring for, maintaining, educate and protect children, develop children according to their abilities, talents and interests and; prevent child marriage.